From Cold War to Cyber War : The Evolution of the International Law of Peace and Armed Conflict over the last 25 Years - Heintze, Hans-Joachim.; Thielbörger, Pierre (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book follows the history of the international law of peace and armed conflict over the last 25 years. It highlights both the parameters that have remained the same over the years as well as the new challenges now facing international law. The articles analyze new developments concerning the prohibition of the use of force in international relations, self-determination of peoples, human rights and human security as well as international coordination of humanitarian assistance.
Part I: Progressive Development of International Law: From Cold War to Cyber War - The Evolution of the International Law of Peace and Armed Conflict over the last 25 Years: An Introduction by Hans-Joachim Heintze and Pierre Thielbörger -- Perspectives of International Humanitarian Law by Knut Ipsen -- Part II: Old Wine in New Bottles: Autonomy and Independence in International Law: Autonomy and Conflict Resolution by Markku Suksi -- Permutations of Popular Sovereignty Before, During and After the Scottish Independence Referendum by Lisa Gow -- Part III: New Threats to International Peace and Security: Climate Change and International Peace and Security: Time for a 'Green' Security Council? by Pierre Thielbörger -- Environmental Migration as a Humanitarian Challenge by Kerstin Rosenow-Williams -- Part IV: New Forms of Warfare and Weaponry: Drones in International Law - The Applicability of Air and Space Law by Stephan Hobe -- "Humanitarian Bombardments" in Jus in Bello? by Robert Kolb -- The Applicability of Article 51 UN Charter to Asymmetric Wars by Peter Hilpold -- Part V: The Changing Role of the Individual in the Law of Peace and Armed Conflict: The Role of the Human Security Perspective by Wolfgang Benedek -- Access to Victims and Humanitarian Assistance by Hans-Joachim Heintze -- Non-Refoulement in International Refugee, Human Rights Law and Asylum Laws by Charlotte Lülf -- Gender in Armed Conflict: The Dimension of Sexual Violence by Wolfgang S. Heinz and Judith Kaiser -- Part VI : Practical Insights on Humanitarian Action and Challenges to the Humanitarian Principles: International Coordination of Humanitarian Assistance by Eltje Aderhold -- Humanitarian Action and Western Military Intervention - a View from Médecins Sans Frontières Germany by Ulrike von Pilar, Corinna Ditscheid and Alfhild Böhringer -- The Role of the German Red Cross as Auxiliary to the Public Authorities in the Humanitarian Field by Sascha Rolf Lüder -- Siding with Rebels - Recognition of Opposition Groups and the Provision of Military Assistance in Libya and Syria (2011-2014) by Christian Schaller -- Civil - Military Relations and International Law by Daniel-Erasmus Khan.
SOL
Book Finder International
Keywords: Climate change; Emigration and immigration; Gender expression; Human rights; International humanitarian law; Sex (Psychology).; International Humanitarian Law, Law of Armed Conflict; Climate Change; Gender Studies; Human Rights; Migration; Law